(Tc(NO)(Cp)(PPh3)Cl) and (Tc(NO)(Cp)(PPh3)(NCCH3))(PF6), and their reactions with pyridine and chalcogen donors - Ernst, Moritz; Abdulkader, Abdullah; Hagenbach, Adelheid; Claude, Guilhem; Roca Jungfer, Maximilian; Abram, Ulrich (Molecules, 2024)
Reactions of the technetium(I) nitrosyl complex [Tc(NO)(Cp)(PPh3)Cl] with triphenylphosphine chalcogenides EPPh3 (E = O, S, Se), and Ag(PF6) in a CH2Cl2/MeOH mixture (v/v, 2/1) result in an exchange of the chlorido ligand and the formation of [Tc(NO)(Cp)(PPh3)(EPPh3)](PF6) compounds. The cationic acetonitrile complex [Tc(NO)(Cp)(PPh3)(NCCH3)]+ is formed when the reaction is conducted in NCCH3 without additional ligands. During the isolation of the corresponding PF6− salt a gradual decomposition of the anion was detected in the solvent mixture applied. The yields and the purity of the product increase when the BF4− salt is used instead. The acetonitrile ligand is bound remarkably strongly to technetium and exchange reactions readily proceed only with strong donors, such as pyridine or ligands with ‘soft’ donor atoms, such as the thioether thioxane. Substitutions on the cyclopentadienyl ring do not significantly influence the ligand exchange behavior of the starting material. 99Tc NMR spectroscopy is a valuable tool for the evaluation of reactions of the complexes of the present study. The extremely large chemical shift range of this method allows the ready detection of corresponding ligand exchange reactions. The observed 99Tc chemical shifts depend on the donor properties of the ligands. DFT calculations support the discussions about the experimental results and provide explanations for some of the unusual findings.